Occupational accident prevention strategies based on Behaviour Based Safety (BBS) in a selected manufacturing industry / Thurga Devi Uthaya Sooriyan - Thurga Devi, Uthaya Sooriyan (2022)
Behavior based safety is defined as an observation made on a particular employee to identify the level of safety practice concern when they perform a job. his study was conducted on the rubber manufacturing industry in Meru, Klang. This study was based on a three-month pilot test observation that took place only during working hours. A total of 152 employees were observed. The goal of this study is to discover the high-potential elements that cause workplace accidents in risky acts and conditions. Not only that, but following the pilot test, to provide a procedure on how BBS can be implemented. Each hazard factor and subfactor discussion included cost-effective ideas for preventing or reducing the number of accident instances. In this study, action plans were considered in relation to the needs of the rubber manufacturing business, and statistical output was analyzed. Due of mischievous behavior, safety behavior is acknowledged to be a main source of accident occurrence. Therefore, several strategies were provided and discussed for a long-term benefit with a slow in progress period. Highly encouraged to conduct safety trainings and frequent assemblies to highlight the importance of safety practice. As for the cost-effective solution for the data collected in this study has been proposed to set up a system which can help to record data’s and to monitor improvements. Safety committees are encouraged to set up an inhouse system for non-conformance tracking and rectifications. For future studies, research study can be done on developing a BBS predictive analytical dashboard system to predict the future outcome hazards and to work on the possible solutions for the hazards.